Is there any Window of Opportunity to Tackle Geriatric Malnutrition? - Khandre, Ruchita Ramesh (Indian Journal of Community Health, 2023)
India has seen an increase in its greying population in recent years. The elderly population has a lot to contribute to society, but various problems like malnutrition can hinder their activities. India has been taking various nutritional interventions but has mainly focused on women and children, while the elderly have been neglected. Even after taking nutritional programmes to national platforms, the sustainability question hovers in the policy makers’ minds. Advanced and novel steps should be taken to ensure the long-term viability of existing programs, which can serve as the foundation for new interventions for the new group. Public health should participate in the new schemes that are currently in place to achieve the other SDGs (Sustainable Development Goals), as the SDG 2030 agenda brings different opportunities to act against malnutrition.